Asuhan Kebidanan Komunitas pada Keluarga Tn. M dengan Anemia Ringan pada Kehamilan di Dusun Mong Desa Kuta Kecamatan Pujut Kabupaten Lombok Tengah Tahun 2024 - Meitia Herawati; Elly Sustiyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The assessment has been carried out by collecting all available data through interview techniques and physical examinations or examinations. Subjective data, especially on the main complaint, namely the mother said she was weak, dizzy, tired quickly, short of breath and pain in the waist and legs. And objective data, namely the mother's general condition is good, anemic conjunctiva and Hb levels of 9.2 g%. Has identified the need for immediate action and collaboration on Mrs. With mild anemia in the Mong Village, Kuta Village with the result that in this case no collaborative action was taken because there were no indications and data to support the action. Has determined a midwifery shelter action plan for Mrs. W with mild anemia in the Mong Village, Kuta Village with the results of care planning based on actual diagnoses/problems and potential problems that can occur. Has carried out the planned care actions for Mrs. W with mild anemia in the Mong Village, Kuta Village with the result that all planned actions can be carried out properly without any obstacles.